La acción de habeas data en el derecho ecuatoriano - Benavides Renteria, Julio Alexander (MACHALA, 2019)
The purpose of the Habeas Data is to protect the person from the abuses that may suffer from the so-called computing power and the consequences that would bring to his honor and good name in case the information disseminated is not true or is wrong. In the present study, it analyzes the jurisdictional action of Habeas Data for the protection of personal information, and its application in the Ecuadorian justice system. In this research work is developed in accordance with the budgets established by the titling system of the Technical University of Machala prior to Obtaining the Degree of Lawyer of the Courts and Tribunals of the Republic of Ecuador.
La finalidad del Hábeas Data es proteger a la persona de los abusos que pueda sufrir respecto del llamado poder informático y de las consecuencias que le traería a su honra y buen nombre en caso de que la información difundida no se veraz o sea errónea. En el presente estudio analiza a la acción jurisdiccional de Hábeas Data para la protección de la información personal, y su aplicación en el sistema de justicia ecuatoriano. En el presente trabajo de investigación se desarrolla de conformidad con los presupuestos establecidos por el sistema de titulación de la Universidad Técnica de Machala previo a la Obtención del Título de Abogado de la Juzgados y Tribunales de la República del Ecuador.
Keywords: GARANTIA HABEAS DATA; INFORMACION PERSONAL; RESPONSABILIDAD DEL ESTADO; HABEAS DATA